2005
DOI: 10.1038/sj.jhh.1001922
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is favourably associated with vascular function in obese Caucasians, but not in obese Africans

Abstract: The comparison of the associations between chronically elevated leptin levels and cardiovascular function in obese Africans and Caucasians has not yet been determined. Therefore, the aim of this study was to compare leptin's associations with cardiovascular function in obese African and obese Caucasian women to determine whether leptin's associations differ between these two groups. This study consisted of two casecase control studies. The first study included a sample of 102 apparently healthy African women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The susceptibility of Africans to cardiovascular abnormalities including hypertension has been widely recognized and suggested to be multifactorial with hyperleptinaemia being regarded as one possible factor. 10 The latter is supported by the present findings revealing positive associations between leptin and Z c in the African but not in the Caucasian women. However, these data should be handled with care since proposed leptin-lowering effects of certain antihypertensive medication 11 might have confounded the results.…”
supporting
confidence: 81%
“…The susceptibility of Africans to cardiovascular abnormalities including hypertension has been widely recognized and suggested to be multifactorial with hyperleptinaemia being regarded as one possible factor. 10 The latter is supported by the present findings revealing positive associations between leptin and Z c in the African but not in the Caucasian women. However, these data should be handled with care since proposed leptin-lowering effects of certain antihypertensive medication 11 might have confounded the results.…”
supporting
confidence: 81%
“…50,51 On the other hand, previous contradictory results have been found regarding ethnic differences in leptin levels. 52,53 Our results show that Africans have higher leptin levels than Caucasians, but it is noteworthy that the African group also recorded a higher BMI than their Caucasian counterparts.…”
Section: Discussionmentioning
confidence: 55%
“…Our research group has recently shown that the leptin levels of obese Caucasian women are favourably associated with vascular function, but this was not evident in obese African women. 31 Even though the results of the correlations (Table 2) of the present study showed strong relationships between inflammatory markers and cardiovascular parameters in both ethnic groups, results showed more and stronger correlations within the Caucasian women. Furthermore, adjustments for age and obesity resulted in no significant correlations between inflammatory markers and cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies show that leptin is not related to ethnicity, 29,30 whereas others do. 31 The question therefore arises whether there is a difference in the levels of inflammation in black Africans compared to Caucasians. If so, this could at least partly explain the relatively high prevalence of hypertension in the African group.…”
Section: Introductionmentioning
confidence: 99%